Peran Guru sebagai Fasilitator dan Katalisator Melalui Teori Konstruktivisme dalam Model Pembelajaran Kontekstual Pendidikan Agama Kristen - Zakharia Victor Harefa; Talizaro Tafonao; Desetina Harefa; Rini Sumanti Sapalakkai; Selvyen Sophia (Sekolah Tinggi Alkitab Jember, 2022)
The purpose of this research is to see the extent to which the role of Christian religious teachers through constructivism theory in the contextual teaching-learning model. One of the main problems found in this paper by the author is the undeveloped proper contextual teaching-learning model. This paper used a qualitative research method to examine the teacher's role as a facilitator and catalyst through constructivism theory in the contextual teaching-learning models of Christian religious education. The analysis process used in this paper is using various source literature, both journal articles, books, and other trusted reference material to support the author’s analysis. The results found in the study indicate that the theory of constructivism in the contextual learning model can be applied by understanding the nature of the contextual learning model, the theory of constructivism, the basic concepts of contextual learning for Christian religious education, and the role of Christian religious education teachers as facilitators and catalysts. Thus, the development of constructivism theory in the contextual learning model of Christian religious education can provide new insights to teachers in carrying out their duties as professional educators. AbstrakTujuan penelitian ini adalah melihat sejauh mana peran guru agama Kristen melalui teori kostruktivisme dalam model pembelajaran kontekstual (Contextual Teaching Learning). Salah pokok permasalah yang ditemukan oleh penulis dalam tulisan ini adalah pengembangan model pembelajaran yang bersifat kontekstual (Contextual Teaching Learning) belum dikembangkan dengan baik. Metode yang digunakan dalam tulisan ini adalah metode penelitian kualitatif dengan mengkaji bagaimana peran guru sebagai fasilitator dan katalisator melalui teori konstruktivisme dalam model pembelajaran kontekstual pendidikan agama Kristen. Proses analisis yang digunakan dalam tulisan ini adalah menggunakan berbagai sumber literatur baik artikel jurnal, buku dan bahan referensi lainnya yang terpercaya untuk mendukung analisis penulis. Hasil yang ditemukan dalam kajian ini menunjukkan bahwa teori konstruktivisme dalam model pembelajaran kontekstual dapat diterapkan dengan memahami hakikat model pembelajaran kontekstual, teori konstruktivisme, konsep dasar pembelajaran kontekstual pendidikan agama Kristen dan peran guru pendidikan agama Kristen sebagai fasilitator dan katalisator.Dengan demikian, pengembangan teori konstruktivismedalam model pembelajaran kontekstual pendidikan agama Kristen dapat memberi wawasan baru kepada guru dalam melaksanakan tugas sebagai pendidik yang profesional.